(untitled) - Altschuler, Max (Hoboken, New Jersey, 2016)
Hacking Sales helps you transform your sales process using the next generation of tools, tactics and strategies. Author Max Altschuler has dedicated his business to helping companies build modern, efficient, high tech sales processes that generate more revenue while using fewer resources. In this book, he shows you the most effective changes you can make, starting today, to evolve your sales and continually raise the bar. You’ll walk through the entire sales process from start to finish, learning critical hacks every step of the way. Find and capture your lowest-hanging fruit at the top of the funnel, build massive lead lists using ICP and TAM, utilize multiple prospecting strategies, perfect your follow-ups, nurture leads, outsource where advantageous, and much more. Build, refine, and enhance your pipeline over time, close deals faster, and use the right tools for the job—this book is your roadmap to fast and efficient revenue growth.
Keywords: Quản lý bán hàng,Sales management